Microplastics and tetracycline affecting apoptosis, enzyme activities and metabolism processes in the Aurelia aurita polyps: insights into combined pollutant effects - Xuandong Wu; Xuandong Wu; Xiaoyong Zhang; Hongze Liao; Jie Guo; Zhenhua Ma; Zhilu Fu; Zhilu Fu (Frontiers in Marine Science)
IntroductionMicroplastics (MPs) and tetracycline (TC) are pervasive contaminants in marine ecosystems, yet their combined effects on benthic organisms, such as Aurelia aurita polyps, remain poorly understood. This study investigates the mechanisms of cellular apoptosis, oxidative stress, and metabolic responses induced by single and combined exposures to MPs and TC.MethodsThree experimental phases were conducted: (1) A 7-day exposure to MPs (1 mg/L) and TC (5 mg/L) to assess apoptosis via TUNEL assay; (2) Short-term high-concentration exposure (MPs: 10 mg/L, TC: 5 mg/L) for 72 hours, followed by a 288-hour recovery period, with antioxidant indicators (CAT, GSH, SOD, MDA, etc.) measured at intervals; (3) Long-term exposure (185 days) to environmentally relevant concentrations of MPs (0–1 mg/L) and TC (0–5 mg/L), with metabolomic profiling via LC-MS and pathway analysis. Polyp cultures were maintained under controlled conditions, and statistical analyses included two-way ANOVA and multivariate models (PCA, OPLS-DA).ResultsThe TUNEL assay revealed significantly higher apoptosis rates in the MPs+TC group compared to controls or single-pollutant groups (P < 0.05). Antioxidant capacity tests indicated persistent oxidative damage in the MPs group even after 288 hours of recovery. Metabolomics identified distinct physiological strategies for MPs and TC, with altered pathways (e.g., ABC transporters, protein digestion) and disrupted metabolites (antioxidants, neurotransmitters). Notably, TC exhibited non-linear toxicity, with high concentrations not consistently exacerbating harm.DiscussionCombined exposure to MPs and TC induced synergistic stress in Aurelia aurita polyps, elevating apoptosis and causing irreversible oxidative damage (e.g., sustained T-AOC decline, MDA accumulation). TC paradoxically mitigated oxidative stress in co-exposure groups, likely via antibacterial effects. Long-term exposure disrupted metabolic pathways (e.g., ABC transporters, arachidonic acid) and neurotransmitter levels, impairing stress resilience and intercellular communication. MPs also altered retinoic acid and indole derivatives, potentially interfering with life-history transitions. While A. aurita exhibited tolerance, persistent damage underscores risks for less resilient benthic species. These findings highlight the need to address cumulative ecological impacts of marine pollutants through enhanced regulation and mechanistic studies.